AI-powered digital transformation – organizational perspective. Literature review - Ewa Chrzanowska; Maciej Chrzanowski; Piotr Zawada (Journal of Modern Science)
The integration of new technologies into all areas of a company existence, known as digital transformation, necessitates a fundamental shift in traditional understanding of a business process optimization and human resilience to turbulent socioeconomical and technological environment. Simultaneously, artificial intelligence (AI) emerges as a disruptive force, with immense potential to impact businesses and individuals on an unprecedented scale and at an (exponential) pace. The purpose of paper is to present the theoretical foundations of the concept of AI-powered digital transformation from an organizational perspective (taking ethical aspects also into account). The main research method is a systematic literature review based on the Web of Science (ELSEVIER) database. On the foundation of literature review, the core pillars of AI-Powered digital transformation are presented as a contribution to further theoretical and empirical research.